2015
DOI: 10.1016/j.cognition.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the approximate number system to quantify the contribution of visual stimulus features

Abstract: The approximate number system (ANS) subserves estimation of the number of items in a set. Typically, ANS function is assessed by requiring participants to compare the number of dots in two arrays. Accuracy is determined by the numerical ratio of the sets being compared, and each participant’s Weber fraction (w) provides a quantitative index of ANS acuity. When making numerical comparisons, however, performance is also influenced by non-numerical features of the stimuli, such as the size and spacing of dots. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
271
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(306 citation statements)
references
References 69 publications
10
271
2
Order By: Relevance
“…Density judgements were biased towards numerosity by about 78% and area by 53%, whereas number judgements were biased towards area by only 15%. This is consistent with several studies that showed small biases of numerosity estimates towards area (DeWind, Adams, Platt, & Brannon, 2015;Gebuis & Reynvoet, 2012a, 2012b, but stronger effects of numerosity on area judgements (Hurewitz, Gelman, & Schnitzer, 2006;Nys & Content, 2012) and density judgments (Dakin et al, 2011). Importantly, the selective sensitivity for numerosity over density is far less pronounced with dense stimuli, where the results are consistent with independent analyses of density and area .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Density judgements were biased towards numerosity by about 78% and area by 53%, whereas number judgements were biased towards area by only 15%. This is consistent with several studies that showed small biases of numerosity estimates towards area (DeWind, Adams, Platt, & Brannon, 2015;Gebuis & Reynvoet, 2012a, 2012b, but stronger effects of numerosity on area judgements (Hurewitz, Gelman, & Schnitzer, 2006;Nys & Content, 2012) and density judgments (Dakin et al, 2011). Importantly, the selective sensitivity for numerosity over density is far less pronounced with dense stimuli, where the results are consistent with independent analyses of density and area .…”
supporting
confidence: 91%
“…This result not only shows that numerosity is not derived indirectly from density, texture or other low-level features, but also casts doubts on the idea that density is a primary visual feature: rather, density seems to be derived indirectly from numerosity, reinforcing previous evidence showing that at low numerosities, density judgments are particularly unreliable and are often surrogated by number judgments . Overall our results add to a growing body of literature showing that visual numerosity is perceived directly, rather than being recalculated from area and density (Anobile, Arrighi, et al, 2016;Anobile, Castaldi, Turi, Tinelli, & Burr, 2016;Anobile et al, 2014;Anobile, Cicchini, et al, 2016;Anobile et al, 2015;Arrighi et al, 2014;Burr & Ross, 2008;Cicchini et al, 2016;DeWind et al, 2015;Hurewitz et al, 2006;Kramer, Di Bono, & Zorzi, 2011;Ross & Burr, 2010Stoianov & Zorzi, 2012).…”
Section: Items Connection Affects Ans and Texture-density 140supporting
confidence: 62%
“…However, while reviews supporting the number sense theory do not discuss confounds and evidential weaknesses, both behavioral and neuroimaging evidence for this proposal are very weak, or even negative: There are practically no fMRI studies which deliver clear evidence and negative findings seem to outweigh positive ones (see Szűcs et al, 2013a,b, for a review). Further, past behavioral data referring the putative impairment of a so-called nonsymbolic number representation are disqualified by major confounds in the stimulus material (Bugden and Ansari, 2015;DeWind et al, 2015;Fuhs and McNeil, 2013;Gilmore et al, 2013;Mix et al, 1997;Szűcs et al, 2013a,b). In addition, it is doubtful whether there is a connection between the magnitude representation and school mathematics achievement at all (see Szűcs et al, 2014 for analysis).…”
Section: Mld and Ddmentioning
confidence: 99%
“…Thus, besides number, size, and spacing, at least seven nonnumerical dimensions can be expressed as a function of those three dimensions: total perimeter, total surface area, individual surface area, field area, sparsity, coverage, and apparent closeness (see ref. 64 for precise mathematical definitions and derivations of the choice model). After estimating the degree to which number, size, and spacing influence each participant's choice behavior (b number , b size , and b spacing respectively), these β estimates were created to form a β vector for behavior.…”
Section: Methodsmentioning
confidence: 99%
“…In recent work, an innovative approach has been developed to provide a statistical test of the effects of numerical and nonnumerical magnitudes on behavior or on neural activity (62)(63)(64)(65). These studies have demonstrated a large effect of numerosity and minimal, if any, effects of nonnumerical cues (such as surface area, sparsity, or spacing) on behavioral measures of numerosity judgment or on neural activity evoked by passively viewing dot arrays of a wide range of numerosities with no explicit task demands on magnitude.…”
Section: Methodsmentioning
confidence: 99%